Movement characteristics influencing intra-individual performance differences in competitions of men`s javelin throw - Makino, M.; Takigawa, H.; Matsubayashi, T. (International Journal of Performance Analysis in Sport, 2025)
This study aimed to investigate the three-dimensional movements influencing intra-individual performance differences in men`s javelin throw competitions. Twenty male javelin throwers participated in one of two competitions. Throwing motions during each attempt were recorded using two digital video cameras. The best and worst recorded attempts by each thrower within the same competition were analysed. The kinematic variables were calculated and compared between attempts. Significant differences were observed in the resultant and forward initial velocities of the javelin and release position between the best and worst attempts. However, there was no significant difference observed in any throwing kinematic variables, except for the trunk counterclockwise rotation angle. These findings indicate that the forward initial velocity of the javelin primarily influences intra-individual performance differences. Movements associated with these differences vary among individuals and do not follow a common pattern.